Who knows not where an anemone does wear his sting? Could polypeptides released from the columnar vesicles of Bunodosoma cangicum induce apoptosis in the ZF-L cell line?. (15th December 2016) - Bastos, Claudio L.Q.; Varela, Antonio Sergio; Ferreira, Shana Pires; Nornberg, Bruna Felix; Boyle, Robert Tew
Abstract: We provide ultrastructural and cytological evidence that the tentacles of the sea anemone Bunodosoma cangicum does not contain cytotoxic venom. However, we show that the stimulated secretion of an apparent mixture of biomolecules containing polypeptides from the columnar vesicles of Bunodosoma cangicum is apparently a potent inducer of apoptosis in the zebrafish cell line, ZF-L. Microscopic fluorescence, cell morphology and flow cytometric assays confirm the apoptotic activity. Crude vesicle venom was partially purified by size exclusion chromatography. PAGE analysis shows that this venom contains low weight polypeptides but no measurable protein. The apoptotic activity is heat labile, and the observed peptides concurrent with this activity have a molecular weight of approximately 2000 Da. This manuscript is the first report of biologically active molecules and peptides associated with columnar vesicles of anemones, and the first to confirm that the tentacles of B. cangicum do not contain cytotoxic venom, and express spirocytes exclusively. Highlights: The tentacle cnidocytes of B. cangicum are exclusively spirocytes. Tentacle tissue of B. cangicum does not contain cytotoxic venom. Columnar vesicles contains polypeptides which induce apoptosis.